2008
DOI: 10.1111/j.1476-5381.2008.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

VIP modulates the pro‐inflammatory maternal response, inducing tolerance to trophoblast cells

Abstract: Background and purpose: Successful embryo implantation is followed by a local pro-inflammatory and Th1 response, subsequently controlled by a Th2 response. Vasoactive intestinal peptide (VIP) has anti-inflammatory effects and promotes tolerogenic/Th2 responses while favouring embryonic development. We investigated the potential regulatory role of VIP on human trophoblast cells, maternal pro-inflammatory responses and trophoblast-maternal leukocyte interactions. Experimental approach: We tested VIP effects dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…The reduced expression of VIP at the sites of implantation of NOD mice confirms and extends the observations on the potential pro-implantatory role of VIP in the human maternal-fetal dialogue recently reported by means of an in vitro approach (Fraccaroli et al 2009). Further studies are needed to address the mechanisms underlying the potential role of VIP as a modulatory factor and the perspectives for its application to therapy of pregnancy failures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The reduced expression of VIP at the sites of implantation of NOD mice confirms and extends the observations on the potential pro-implantatory role of VIP in the human maternal-fetal dialogue recently reported by means of an in vitro approach (Fraccaroli et al 2009). Further studies are needed to address the mechanisms underlying the potential role of VIP as a modulatory factor and the perspectives for its application to therapy of pregnancy failures.…”
Section: Discussionsupporting
confidence: 88%
“…We have recently reported on the expression of VIP and VIPR1 in a human trophoblast cell line (Fraccaroli et al 2009). By means of an experimental approach to the human fetal-maternal interface, we showed the participation of endogenous VIP in the fetalmaternal interaction with a pro-implantatory role by increasing the expression of Treg markers and LIF (Fraccaroli et al 2009). Other authors have reported on the ability of VIP to modulate hCG and progesterone in human trophoblast cultures (Marzioni et al 2005) and to be selectively concentrated in the uterine vasculature, where its levels have been reported to be 2.5-fold greater than in maternal blood (Ottesen et al 1982).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…VIP also has anti-inflammatory effects and, like progesterone, promotes a Th2 shift through the stimulation of IL10. DCs differentiated in the presence of VIP induce T regs , inhibiting allogeneic CD4 responses and increasing TGFB, suggesting a dual responsibility at the maternal-fetal interface (Fraccaroli et al 2009). …”
Section: Anti-inflammatory Vipmentioning
confidence: 99%
“…In this model, VIP increased the frequency of maternal CD4+CD25+Foxp3+ cells, TGF-β expression, and IL-10 secretion. Accordingly, it reduced proinflammatory mediators such as MCP-1, IL-6, and nitric oxide production [26]. …”
Section: Introductionmentioning
confidence: 99%